2014
DOI: 10.1371/journal.pone.0097838
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium Butyrate as an Alternative to Dietary Fiber: Effects on the Embryonic Development and Anti-Oxidative Capacity of Rats

Abstract: In this study, we evaluated the effect of replacing dietary fiber with sodium butyrate on reproductive performance and antioxidant defense in a high fat diet during pregnancy by using a rat model. Eighty virgin female Sprague Dawley rats were fed one of four diets—(1) control diet (C group), (2) high fat + high fiber diet (HF group), (3) high-fat +5% sodium butyrate diet (SB group), and (4) HF diet + α-cyano-4-hydroxy cinnamic acid (CHC group)—intraperitoneally on days 8, 10, 12, 14, and 16 of gestation. SB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
1
22
1
Order By: Relevance
“…In a rodent obesity model, both supplementation with butyrate and oral administration of acetate have been demonstrated to suppress weight gain [ 12 ]. In a maternal diet, supplementing with butyrate has been shown to increase reproductive performance and enhanced anti-oxidant capacity [ 28 ]. In the present study, we demonstrated for the first time (as far as we know) the influence of a butyrate supplement on maternal and offspring lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a rodent obesity model, both supplementation with butyrate and oral administration of acetate have been demonstrated to suppress weight gain [ 12 ]. In a maternal diet, supplementing with butyrate has been shown to increase reproductive performance and enhanced anti-oxidant capacity [ 28 ]. In the present study, we demonstrated for the first time (as far as we know) the influence of a butyrate supplement on maternal and offspring lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sodium butyrate during pregnancy in a rat model increased the expression of antioxidant and nutrient-related genes. 32 In pigs, sodium butyrate supplementation improved embryo development in vitro and enhanced gene expression involved in early development. 33,34 Lastly, a recent study in rats suggested that hypertension was associated with reductions in the proportions of butyrate-producing bacteria but increases in bacteria that produce lactate.…”
Section: Hypertensionmentioning
confidence: 99%
“…Butyrate supplementation to gestating sows has been reported to enhance post-weaning growth performance of offspring ( 13 ) , although supplementation with sodium butyrate after farrowing did not have a significant effect on weaning body weight ( 31 ) . It has also been shown that butyrate supplementation of high-fat diet-fed mothers increased the number of fetuses compared with the control group ( 12 ) . Butyrate can act as a growth promoter in milk replacement formula for young calves ( 32 ) .…”
Section: Discussionmentioning
confidence: 99%
“…After birth, butyrate can be directly ingested by the neonates ( 37 ) . For butyrate crossing the placenta, previous studies have shown that multiple subtypes of maternal monocarboxylate transporters (MCT) were expressed ( 38 ) in the placenta, and maternal high-fat diets with butyrate could increase MCT mRNA expression in the placenta ( 12 ) . Thus, our present study speculated that maternal butyrate supplementation during gestation and lactation could cross the placental barrier of dams and pass through milk of dams to offspring to influence offspring skeletal muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation